2011
DOI: 10.1021/ef200510e
|View full text |Cite
|
Sign up to set email alerts
|

Gas Production from Methane-Hydrate-Bearing Sands by Ethylene Glycol Injection Using a Three-Dimensional Reactor

Abstract: The gas production from methane-hydrate-bearing sediment by injecting ethylene glycol (EG) solution was investigated using a three-dimensional experimental apparatus. Eight experimental runs were performed to examine the influence of operation conditions on hydrate dissociation by EG injection. The variations of pressure and temperature distribution in the reactor stimulated by the injected EG were obtained for the gas production process of the hydrate. The variation trend of temperature in the injection stage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
84
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 134 publications
(85 citation statements)
references
References 20 publications
1
84
0
Order By: Relevance
“…These studies also reported the existence of an optimal 'production efficiency', defined as volumetric rate of gas recovered per unit mass of EG injected. This optimum amount of inhibitor was later found to be related to the pore volume below the well inlet [147]. It has also been reported that the presence of inhibitor lowers the heat of dissociation which improves heat efficiency by approximately 3.5 times according to the concentration of inhibitor [144].…”
Section: Chemical Inhibitor Injectionmentioning
confidence: 83%
See 1 more Smart Citation
“…These studies also reported the existence of an optimal 'production efficiency', defined as volumetric rate of gas recovered per unit mass of EG injected. This optimum amount of inhibitor was later found to be related to the pore volume below the well inlet [147]. It has also been reported that the presence of inhibitor lowers the heat of dissociation which improves heat efficiency by approximately 3.5 times according to the concentration of inhibitor [144].…”
Section: Chemical Inhibitor Injectionmentioning
confidence: 83%
“…Increasing EG concentration generally results in an increased gas production ratio [146,147]. These studies also reported the existence of an optimal 'production efficiency', defined as volumetric rate of gas recovered per unit mass of EG injected.…”
Section: Chemical Inhibitor Injectionmentioning
confidence: 90%
“…To make the utilization of this resource economically viable, it is imperative to exploit the gas from the hydrate reservoir effectively and safely. The major potential methods for producing gas from hydrates are depressurization [11][12][13], thermal stimulation [14][15][16][17][18], inhibitor stimulation [19][20][21][22], and carbon dioxide replacement [23][24][25]. The depressurization is considered as the most economically feasible and the least energy intensive method.…”
Section: Introductionmentioning
confidence: 99%
“…It was found that the gas production rate tends to reduce significantly if the brine concentration is excessively high. Our group investigated the gas production from methane hydrate-bearing sands by ethylene glycol injection using a three-dimensional apparatus [107]. As shown in Figure 9, there exists an optimal value of mass ratio of injected ethylene glycol solution to initial water, where a maximum gas production ratio appears.…”
Section: Chemical Injection Methodsmentioning
confidence: 99%
“…Figure 9. Variation of the gas production ratio with R EG-w (the ratio of injected ethylene glycol solution mass to the initial water mass) [107]. …”
Section: Chemical Injection Methodsmentioning
confidence: 99%